Comparisons and implications of alternative views of the Soviet economy - Hopkins, Mark Myron; Kennedy, Michael, 1949-; Rand eBooks (Santa Monica, CA : RAND, 1984)
This report uses the Hopkins-Kennedy optimal control model of the Soviet Union to explore the implications of and make comparisons between three "worlds" (views) that hold differing assumptions concerning the nature of the Soviet economy. These are the "Birman world," the "CIA world," and the "Rosefielde-Lee world." A secondary object is to investigate a large number of scenarios concerning foreign trade so as to improve understanding of this important aspect of the Soviet economy.
"March 1984."
This research was conducted under RAND's National Defense Research Institute.
Includes bibliographical references (p. 75-77).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Soviet Union -- Economic conditions -- 1975-1985.; Electronic books